Analysis of the Interest of the Chinese Government in the Xinjiang Region in the Uyghur Muslim Ethnic Conflict - Nurhidayati, Nurhidayati; Rahayu, Riva; Utari, Tituk; Nurhamzah, Nurhamzah; Efendi, Muhsin; Amin, Fakhry (HK-Publishing, 2022)
AbstractMuslims in China are one of the minority ethnic groups that still exist today. Ethnic Hui and Uyghurs are among Chinaâ€™s most significant ethnic minority Muslims. The Uyghur Ethnic Conflict was based on discrimination by the Chinese government against Uyghur Muslims, which later led to anarchic acts and policies of persecution of the Chinese government towards Uyghur ethnicity. This study looks at the interests of the Chinese state government in the Xinjiang region in the occurrence of Uyghur Muslim ethnic conflicts. The approach used in this research is qualitative. Then the data used in this study comes from various research results and previous studies that are still related to the Uyghur Muslim ethnic conflict. This study found that the Uyghur Muslim ethnic group in Xinjian felt injustice, so they asked the Chinese government to separate Xinjian from China. Then this conflict is getting worse because the Chinese government uses violence and violates human rights. Despite getting a lot of criticism from various parts of the world, China still carries out this repression for its economic purposes.Keywords: Uyghur Muslims, China, Interest, Ethnic Conflict, Xinjiang.Â AbstrakMuslim di China merupakan salah satu etnis minoritas yang masih eksis hingga saat ini. Etnis Hui dan Uyghur adalah salah satu etnis minoritas Muslim paling signifikan di China. Konflik Etnis Uyghur didasari oleh diskriminasi yang dilakukan pemerintah China terhadap Muslim Uyghur, yang kemudian berujung pada tindakan anarkis dan kebijakan persekusi pemerintah China terhadap etnis Uyghur. Penelitian ini melihat kepentingan pemerintah negara China di wilayah Xinjiang dalam terjadinya konflik etnis Muslim Uyghur. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif. Kemudian data yang digunakan dalam penelitian ini berasal dari berbagai hasil penelitian dan penelitian sebelumnya yang masih terkait dengan konflik etnis Muslim Uyghur. Penelitian ini menemukan bahwa kelompok etnis Muslim Uyghur di Xinjian merasakan ketidakadilan, sehingga mereka meminta pemerintah China untuk memisahkan Xinjian dari China. Kemudian konflik ini semakin parah karena pemerintah China menggunakan kekerasan dan melanggar hak asasi manusia. Meski mendapat banyak kritik dari berbagai belahan dunia, China tetap melakukan represi ini untuk kepentingan ekonominya.Kata kunci: Muslim Uyghur, Cina, Kepentingan, Konflik Etnis, Xinjiang.